Utilization of ursolic acid methyl ester in the treatment of Streptococcus pyogenes in Nile tilapia, concerning physiological, genetic, immune-oxidative, stress, and neuro-ethological parameters - Rewan Abdelaziz; Mona Abd El khalek Salem; Walaa El-Houseiny; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Heba H. Mahboub; Shimaa Zayed; Reham A. Abd El-Wahab; Basma A. Elshafey; Simon J. Davies; Amany Omar Selim (Aquaculture Reports)
The present work is an innovative approach for application the Streptomyces misakiensis S. misakiensis metabolite called ursolic acid methyl ester (UAME) in treating Streptococcus pyogenes of Nile tilapia. A total of 110 fish was used for assessment of the therapeutic dose of UAME. In addition, the therapeutic efficacy of UAME was tested in vivo against S. pyogenes infection (after determination of LC50) using 200 Nile tilapia. Fish (30.00 ± 1.5 g) were divided into four groups: CON (control), UAME (1.0 mg/L), S. pyogenes, and UAME (1.0 mg/L) + S. pyogenes groups. The inoculations of 0.2 mL of S. pyogenes (1 ×107 CFU/mL) were administered to the fish in the S. pyogenes and UAME + S. pyogenes groups and continued for ten days. The minimal inhibitory concentration of UAME was 0.5 µg/mL. Moreover, irregularity and bacterial cell shape distortion were evident after treatment with UAME under a scanning Electron Microscope. Challenged groups in S. pyogenes exhibited significant increases in surfacing frequency, swimming, laterality and aggression behavior (P < 0.05). Along with this, the hepatorenal metrics (ALT, ALP, AST, creatinine, total bilirubin, and urea.), MDA (an oxidant biomarker), (8-OHdG), glucose and cortisol (stress indicators) were all significantly elevated in the diseased fish (P < 0.05). Contrariwise, the infected fish showed a significant drop (P < 0.05) in survival %, red blood cells, hemoglobin, total proteins, total globulin, albumin, AchE activity, and the immune-antioxidant indices (IgM, complement factor 3, lysozyme activity, nitric oxide, hepatic CAT, SOD, GSH, and GPx). Analysis of genes in response to S. pyogenes infection demonstrated an up-regulation of the pro/anti-inflammatory genes (il1b, tnfa, il8, tgfb, il10). Surprisingly, enriched groups in UAME modulated all the measured parameters. Overall, UAME is a promising antibacterial candidate that can efficiently retrieve stress and enhance behavioral, biochemical, immune-antioxidant, and genetic changes endowed by S. pyogenes infection.